Coolie Town, St.James, Trinidad - Rice, Ben (My University, 2010)
Former indentured labourers, buy and selling on the street in St. James.
Colour: Black and white; Style: Landscape; Other: Unbordered; Divided
Keywords: Trinidad and Tobago; Postcards; Rural villages--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--St. James; Dwellings--Trinidad and Tobago; East Indians--Trinidad and Tobago